Immunosuppressive Treatment in Antiphospholipid Syndrome: Is It Worth It? - Ilaria Mormile; Francescopaolo Granata; Alessandra Punziano; Amato de Paulis; Francesca Wanda Rossi (Biomedicines, 2021)
The antiphospholipid syndrome (APS) is characterized by the development of venous and/or arterial thrombosis and pregnancy morbidity in patients with persistent antiphospholipid antibodies (aPL). Catastrophic antiphospholipid syndrome (CAPS) is a life-threatening form of APS occurring in about 1% of cases. Lifelong anticoagulation with vitamin K antagonists remains the cornerstone of the therapy for thrombotic APS, but frequently the use of anticoagulation may be problematic due to the increased risk of bleeding, drug interactions, or comorbidities. Immunosuppressant drugs are widely used to treat several autoimmune conditions, in which their safety and effectiveness have been largely demonstrated. Similar evidence in the treatment of primary APS is limited to case reports or case series, and studies on a large scale lack. Immunomodulatory drugs may be an emerging tool in managing such particular situations, like refractory obstetrical complications, CAPS, or so-called APS non-criteria manifestations. In addition, immunomodulatory drugs may be useful in patients experiencing recurrent thromboembolic events despite optimized anticoagulant therapy. We did a comprehensive review of literature analyzing the possible role of immunomodulation in primary APS to provide a broad overview of potentially safe and effective target treatments for managing this devastating disease.